2014
DOI: 10.2215/cjn.05190514
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Reporting of AKI in Very Low Birth Weight Infants

Abstract: AKI occurred in 40% of very low birth weight infants and was concentrated in the most premature and severely ill infants. One in six infants experienced multiple episodes of AKI, and a small number of infants was discharged with an elevated serum creatinine. Reporting a history of AKI in the discharge summary occurred infrequently, and referral to a nephrologist for AKI follow-up did not occur, highlighting areas for quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
157
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(177 citation statements)
references
References 51 publications
16
157
1
3
Order By: Relevance
“…Here, we report a much higher incidence of AKI of 50.9%, which likely reflects several factors. First, mild degrees of AKI are commonly overlooked and not recorded on the discharge summary (18,19). Second, we used a standardized definition of AKI, which undoubtedly led to increased recognition of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report a much higher incidence of AKI of 50.9%, which likely reflects several factors. First, mild degrees of AKI are commonly overlooked and not recorded on the discharge summary (18,19). Second, we used a standardized definition of AKI, which undoubtedly led to increased recognition of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…10,65,66 In 2011, Koralkar et al 10 reported on 229 VLBW infants followed prospectively from birth until 36 weeks postmenstrual age. The incidence of AKI, by using the neonatal modified KDIGO criteria, was 18%.…”
Section: Vlbw and Elbw Neonatesmentioning
confidence: 99%
“…The risk of neonatal AKI increases with increasing degree of prematurity, demonstrating a dose-response effect in the susceptibility of the developing kidney to injury [159]. Neonatal AKI is associated with poor short-term outcomes, such as increased mortality and longer hospital stays [159,160].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%
“…Neonatal AKI is associated with poor short-term outcomes, such as increased mortality and longer hospital stays [159,160]. In addition to the association between neonatal AKI and short-term outcomes, AKI is linked to the development of CKD both in epidemiology studies and in studies of LBW subjects (weighing <1.5 or 1.0 kg), an effect that may be modulated by the development of obesity [20,161,162,163,164].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%